Crop Planting Structure Optimization for Water Scarcity Alleviation in China. (23rd May 2016) - Zhang, Lijia; Yin, Xin'an; Xu, Zhihao; Zhi, Yuan; Yang, Zhifeng
Summary: Along with globalization, countries consume a large amount of goods and services from both domestic and international markets. As one of the world's largest agricultural countries, China is faced with serious water scarcity and has to reduce the water consumption from both domestic and global aspects, of which the crop planting structure optimization (CPSO) between regions based on the virtual water perspective could be a solution for efficient agricultural water consumption. In this article, three scenarios of Chinese agriculture, including agricultural water consumption restrictions relaxed scenario, agricultural water consumption limited scenario, and net utilization ratio of water resources limited scenario, were designed to minimize the national agricultural water consumption under various water, land, and crop planting constraints in individual provinces and analyze the impacts of the CPSO. The results showed that compared with the historical situation of crop planting in 2007, 53.3%, 51.4%, and 47.3% of the agricultural water consumption and more than 10% of the sown area of China was saved under the three scenarios, respectively. Because of the reduction of agricultural water consumption and land use, it brought about the expansion of crops production in China. CPSO is found to have notable effects on water saving and food security considering the dependence of the crops by international trade.